Changing community, changing practice? Young gay men, HIV and gay community - Fraser, Suzanne (UNSW Sydney, 2004)
This project is a qualitative study of young gay men in Sydney. It is aimed at accessing some of the ways in which young men identify sexually, how they feel about notions of community - gay community n particular - and their perceptions of safe sex. Funded by NSW Health, the study emerged out of discussions conducted within the NSW HIV sextor. These focused on questions around the changing character of gay community.
Monograph 1/2004
Keywords: Sexual identity; Youth; Gay men; Community; Safe sex; HIV; Transmission; Testing; Risk perception; Drug use; Australia